Empowering Mahasantri Community In Developing Open Educational Resources On Ecological-Based Islamic Education Learning - Anam, Nurul; Syaehotin, Sayyidah (Universitas Nurul Jadid, 2024)
Currently, society is confronted with highly significant issues. These issues pose significant concerns caused of global climate change and the advent of Society 5.0. The Department of Islamic Education in Islamic higher education may encounter these issues. The department is responsible for producing competent prospective teachers who are capable of adapting to contemporary advancements. Indeed, the findings of the preliminary study indicate that students enrolled in the Department of Islamic Education at IAI Al-Qodiri Jember seems to be insufficiently prepared to confront these two highly significant challenges. Thus, this community service aimed to empower mahasantri by enabling them to create an open educational resource for Ecological-based Islamic Education learning. The objective was to equip them with the necessary knowledge and skills to address the challenges posed by global climate change and the Society 5.0 era. The community service used the Community-based Research (CBR) method. The findings resulted some points. First, students in the department exhibited an awareness to confront the challenges they encountered and fostered a desire among students to promote changes through the educational-oriented open educational resources movements. Secondly. students were capable of generating advancements in the form of IT-based Islamic Education learning materials and instructional media. Thirdly, students demonstrated the ability to create diverse products through the process of developing learning media, specifically open educational resources that encompassed materials and other Ecological-based Islamic Education learning activities.